The transcendence of the face: A semiotic-linguistic path - Volli, Ugo (Sign Systems Studies, 2021)
This paper starts with an examination of the terms used to designate the face in different languages, in particular in Italian, comparing these with the definitions provided by some authoritative dictionaries as well as with their etymology. This exploration yields some remarkable results: firstly, it appears that the face is indeed a term that has a material meaning, but at the same time it is a social object; secondly, the importance of the communicative function emerges, which makes the face similar to the mask and in some ways to the arbitrariness of language. All this suggests that the philosophical status of the face is that of ‘transcendence’ which is a condition of that state of freedom that we attribute to ourselves and that can be defined as ‘human exception’.